1995
DOI: 10.1177/036354659502300613
|View full text |Cite
|
Sign up to set email alerts
|

Graft Site Morbidity with Autogenous Semitendinosus and Gracilis Tendons

Abstract: To distinguish between morbidity caused by harvesting semitendinosus and gracilis tendons and morbidity associated with anterior cruciate ligament reconstruction surgery, we performed a prospective randomized study using 65 patients who underwent anterior cruciate ligament reconstruction using these tendons. The patients underwent either contralateral (N = 34) or ipsilateral (N = 31) graft harvest. For the nonoperated knees in the ipsilateral harvest group, isometric and isokinetic strength of the quadriceps a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
223
4
6

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 354 publications
(242 citation statements)
references
References 29 publications
9
223
4
6
Order By: Relevance
“…Experiments with the tendon of beagle dogs showed similar levels of failure with three difference methods of fixation [11,27,28], with the grafts always failing at the interface between the tendon and the fixation material.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Experiments with the tendon of beagle dogs showed similar levels of failure with three difference methods of fixation [11,27,28], with the grafts always failing at the interface between the tendon and the fixation material.…”
Section: Discussionmentioning
confidence: 85%
“…The volume of the STG graft is greater than that of the BTB [12,17,27], but the difference in the procedures appears to be in the healing which takes place within the bony tunnel. In the STG procedure anchoring begins at the interface of the tendon and the bone and experience has suggested that tendon anchoring takes longer to become sound than bone to bone fixation [14].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Bone-patellar tendon-bone (BPTB) and hamstring tendon autografts are the most commonly used grafts of choice today. Nevertheless, reports of donor-site morbidity have increased [2,3] and the use of artificial ligaments which avoids those complications may offer an alternative form of treatment. The LARS artificial ligament (Ligament Advanced Reinforcement System, Surgical Implants and Devices, Arc-sur-Tille, France) has recently been reported to be a suitable material [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies report deficits in quadriceps and hamstring strength after ACLR, and in many cases, these deficits persist well after the cessation of rehabilitation (Pinczewski et al, 2007;Yasuda, Tsujino, Ohkoshi, Tanabe, & Kaneda, 1995).…”
Section: Introductionmentioning
confidence: 99%